A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini) - Baiocchi, Daniele; Magnani, Gianluca (Zootaxa, 2018)
The Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group is defined and revised. A new species from Turkey, A. (A.) cebecii sp. nov., is described and compared to its most similar species. A. midas oberthuri Schaefer, 1938 is elevated to the rank of species, and a lectotype is designated. A. (A.) spathuligera Obenberger, 1924 and A. (A.) midas muelleri Obenberger, 1925 are reconfirmed synonyms of A. midas Kiesenwetter, 1857. All species of the new species-group are illustrated, including the hitherto unknown male of A. (A.) patsyae Baiocchi, 2008, all type specimens and original data labels. In addition to diagnostic characters, informations on the distribution, biology and taxonomic position of each species are also presented, together with a short definition of the new species-group, and a key to its species.